The Development of Bank Crediting to Trade Based on Supply Chains in Russia in the Crisis Uncertainty Context - Mariia Nikolaevna Koniagina; Irina Urievna Evstafeva; Viktoriya Valeryevna Manuylenko; Alvi Adlanovich Khashaev; Alena Valerevna Kirillova (International Journal of Supply Chain Management, 2019)
The geopolitical background of Russian trade and banking remains pessimistic, which stresses the importance of studying the experience gained over the past decade and the relevance of the questions raised. In addition, some problems that emerge during trade bank crediting are not so obvious. Talking about them is not common due to a bank’s damaged reputation or a decline in the quotation of trade or credit organization securities. This situation is facilitated by a small size of the Russian securities market, low investment activity of the population, and professional communities isolated from one another, which is typical for Russia. To identify the current challenges encountered in relation to the organization of trade bank crediting and to work out proposals to improve banking when crediting trading companies, the authors analyze the major results of the trade crediting activity of Russian commercial banks between 2009 and 2017; they explain how economic volatility and uncertainty affect the credit risk of banks, and provide an estimate of the development prospects for bank crediting for trading companies. This study uses regression analysis, systematization, generalization, visualization, and economic forecasting methods. The research has determined that the capital adequacy of a number of Russian banks that extensively lend to commercial enterprises is in jeopardy, as in unstable environments the rates of net trading margin and bank profitability are dropping. As a result, the capital expansion resources are limited. At the same time, the need for state support for certain banks under recessional conditions remains a controversial issue with ambiguous implications of such decisions.